Cultural Identity in the Digital Age: A Humanities Perspective - Soumya R (AG Volumes, 2025)
From its beginnings in the 19th century, coinciding with the dawn of a new industrial period, to the sophisticated, cutting-edge technical digital media tools available to us today, digital media has changed throughout time. Around the world, technology is a major factor in forming cultural identities and customs. The increasing impact of globalisation in the digital era is changing cultural identities. Examine the many studies on cultural identity and digital age that have been published in this article. The review reveals that digital media serve as both a catalyst for cultural expression and a threat to cultural distinctiveness. While offering platforms for cultural preservation and global connectivity, digital tools also risk reinforcing cultural homogenization and power imbalances. Particularly among youth in rural India, social media reshapes self-identity, social values, and cultural norms. The study emphasizes the need for context-sensitive strategies that promote digital literacy, algorithmic fairness, and the celebration of local content. A humanities perspective highlights the reciprocal relationship between technology and culture, urging mindful integration to ensure cultural resilience and diversity in the digital age.